Complex Lexical Units Compounds and Multi-Word Expressions - Schlücker, Barbara (Konvergenz und Divergenz, 2019)
The volume explores compounds and multi-word expressions and their interrelation regarding their status in lexicon and grammar in a variety of European languages, including a contrastive overview with a focus on German. It brings together insights from word-formation theory, phraseology and theory of grammar and aims to contribute to the understanding of the lexicon, both from a language-specific and cross-linguistic perspective.